Branchiomeric Muscle Development Requires Proper Retinoic Acid Signaling - Wang, Qi; Xu, Lin; Miura, Jiro; Saha, Mithun Kumar; Uemura, Yume; Sandell, Lisa L.; Trainor, Paul A.; Yamashiro, Takashi; Kurosaka, Hiroshi (Frontiers in Cell and Developmental Biology, 2021)
The first and second branchiomeric (branchial arch) muscles, known as part of the craniofacial muscles, derive from branchiomeric arch mesoderm. This set of muscles is indispensable for operating jaw movement and facial expression. Embryonic failure of developing these muscles could result in congenital partial absence of facial muscles and have significant impact on patients’ quality of life. However, the detailed molecular or cellular mechanism of branchiomeric muscle development is still elusive. Herein we investigated the role of retinoic acid (RA) signaling in developing branchiomeric muscle by using mice as a model. We administered all-trans RA (25 mg/kg body weight) to ICR pregnant mice by gastric intubation from E8.5 to E10.5. In their embryos at E13.5, we found that muscles derived from the first branchial arch (temporalis, masseter) and second branchial arch (frontalis, orbitalis oculi) were absent, while other craniofacial muscles were hypoplastic. We further detected elevated cell death in the branchial arch mesoderm cells in the RA-treated group. These results strongly suggest excessive RA signaling could reduce the survival rate of the precursor cells of branchiomeric muscles, which results in hypoplastic facial muscle development. In order to uncover a signaling pathway(s) underlying this etiology, we focused on Pitx2, Tbx1 and Myod1, critical genes for cranial muscle development. Noticeable reduction of expression of all of these genes was detected in the first and second branchial arch of RA-treated embryos. Moreover, overdose RA signaling induced proximal loss of Dlx5 and Dlx6 expression in cranial neural crest cells, which disrupt the interaction with branchiomeric mesoderm cells. Altogether, we discovered that embryonic branchiomeric muscle defects caused by excessive RA signaling were associated with the reduction of the survival rate of the muscle precursor cells through the downregulation of Pitx2, Tbx1, Myod1 and Dlx5/6.